Misplacement of Tracheostomy Tube in the Right Main Bronchus: a Rare Complication - Armin Amirian; Reza Shahriarirad; Bizhan Ziaian; Parviz Mardani; Amirhossein Erfani (Case Reports in Surgery)
A 38-year-old woman known case of metastatic squamous cell carcinoma of the cervical esophagus due to increasing dyspnea and stridor attributed to the pressure effect of the primary mass was scheduled for tracheostomy, which ended up in the right main bronchus. This rare complication occurred using a tracheostomy tube number 7.5 via a vertical tracheotomy over 4th and 5th tracheal rings. The misplacement was confirmed by chest X-ray and fiberoptic bronchoscopy, and the tracheostomy tube was successfully repositioned in a nonoperative approach.